Indonesia, the Cold War and Non-Alignment: Relations of the Early Indonesian Cabinets with the United States, 1950-52* (Journal of International Studies, 2020)
Indonesia, the Cold War and Non-alignment: Relations of the Early Indonesian Cabinets with the United States, 1950-1952. The Cold War initially focused on Europe but promptly spread to encompass the entire globe. By the early 1950s, the Cold War belligerents began to compete for the allegiance of the newly independent nations. Many of the newly independent nations, however, had from the outset, preferred not to choose sides in the Cold War. India, Burma and Indonesia had all purported to pursue a policy of neutralism and non-alignment in the Cold War. This paper discusses the attempts of the newly independent Republic of Indonesia to steer a policy of nonalignment in the Cold War and the challenges thereto posed by the United States' Cold War policies during the early 1950s. It traces the experiences of the Hatta, Natsir and Sukiman cabinets, 1950-1952. The central theme of the paper is the interplay between the Indonesian policy of non-alignment in the Cold War and the US policy of containment. The paper argues that despite their profession to non-alignment, the early Indonesian cabinets had leaned towards the United States. Indonesia fell with the Anglo-American economic and military orbit. Desirous of American aid, Indonesia increasingly compromised on its stance of nonalignment in the Cold War. The dilemma of dependence proved to be a major stumbling block in Indonesia's attempt to pursue non-alignment.